The Influence of Social Media, Economic Literacy and Digital Literacy on Entrepreneurial Intentions of Class Xi Students (Case Study At Sma N 12 Jakarta) - Nissa Nur Awaliyah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to determine the effect of social media, economic literacy, and digital literacy on entrepreneurial intention of grade XI students of SMA N 12 Jakarta. This study uses a quantitative approach with data collection techniques through questionnaires. The study apopulation was 215 high school students with a sample of 68 students. Data analysis techniques using SEM PLS version 4.0.2. The research instrument used a 5-point Likert scale to measure the level of respondent agreement. Hypothesis testing was carried out with a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) version 4.0.2, through the Outer Model stage (measurement model test). The results showed that social media has a positive effect, economic literacy has a positive and significant effect, and digital literacy has a negative and insignificant effect on entrepreneurial intentions of grade XI students of SMA N 12 Jakarta. Researchers suggest that students in grade XI of SMA N 12 Jakarta increase their use of social media and digital economic literacy. For future researchers, it is recommended to analyze other factors besides social media and digital economic literacy outside of this study.